The sustainable nation : politics, economy and justice - Leonard, Liam (Bingley, U.K. : Emerald Publishing Limited, 2017)
Drawing on almost 20 years of Liam Leonard's research in the field, The Sustainable Nation: Politics, Economy and Justice provides a detailed case study of a modern European state's tumultuous development through first decades of the Millennium. As the Republic of Ireland experienced an initial phase of accelerated growth, followed by a dramatic economic downturn, the nation's attempts to expand its infrastructure was met with resistance from communities concerned about local environments. The Sustainable Nation: Politics, Economy and Justice looks at some of the conflicts that emerged as part of the Irish people's attempts to achieve a sustainable form of development. Other issues such as the rise of a multicultural and globalized society as well as issues of social justice are also explored within this study. This book represents a culmination of Leonard's research on Ireland which began at the turn of the Millennium. The book provides an in depth and up to date study on Ireland's growth and the substantial changes experienced there during the last two decades.
Prelims -- Introduction: the Irish State, from boom to bailout to Brexit -- Economy and resistance -- Conservation -- Water -- Resources -- Energy -- Crime -- Multiculturalism -- Restorative Justice -- Prisons -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Ireland -- Politics and government -- 21st century; Ireland -- Economic conditions -- 1949-; Social justice -- Ireland; Ireland -- Social conditions -- 21st century